The relationship between mother's age and parity and the incident of hypertension in pregnant women at Kayuagung Hospital year 2022 - Dana, Berlian; Agustina, Dessy; Ramadhani, Indri (Institute of Computer Science (IOCS), 2024)
Hypertension in pregnancy is an increase in blood pressure that occurs during pregnancy, with systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥ 90 mmHg in women who were previously normotensive. The purpose of this study was to determine the relationship between age, parity and the incidence of hypertension in pregnant women at Kayuagung Hospital in 2022. The research method is a quantitative, analytic serve method using a cross sectional approach, taking total sampling. The population in this study were 85 samples. The data collection instrument was in the form of a checklist sheet with univariate and bivariate analysis techniques with data analysis using Chi-Square p value = 0.003 there was a significant relationship between maternal age and the incidence of hypertension in pregnant women, p value = 0.003 there was a significant relationship between parity with the incidence of hypertension in pregnant women. The conclusion obtained from the study is that there is a relationship between age and maternal parity with the incidence of hypertension in pregnant women.